Process Capability Analysis in Single and Multiple Batch Manufacturing Systems - Prof. Viraj V Atre (International Journal of Engineering and Management Research, 2018)
Any process, manufacturing or service in operations is subject to constant variation. The underlying principle of variation is any process / rather all processes are subject to changes occurring due to the magical 5 M’s that make the basis of operations management namely: Man, Machines, Materials, Methods and Money. This paper discusses about establishment of a capable process, by means of stabilizing the 5 M’s and studying the variations which occur by going deeply into the well known term used in operations: RCA : Root Cause Analysis.